Delivery of Stimulator of Interferon Genes (STING) Agonist Using Polypeptide‐Modified Dendrimer Nanoparticles in the Treatment of Melanoma. Issue 7 (9th April 2021) - Dosta, Pere; Cryer, Alexander M.; Prado, Michaela; Dion, Michelle Z.; Ferber, Shiran; Kalash, Santhosh; Artzi, Natalie
Abstract : The activation of stimulator of interferon genes (STING) in the cytosol by cyclic dinucleotides (CDNs) enhances antitumor immunity through the induction of proinflammatory cytokines, such as type‐I interferons (IFN‐I). However, the high hydrophilicity and negative charge of CDNs hinders their delivery into cells. Here, by developing a library of cationic polypeptide‐modified dendrimers, it is shown that CDNs can be efficiently delivered intracellularly in vitro and in vivo. With respect to naked dendrimers, generation‐5 polyamidoamine (G5‐PAMAM) dendrimers modified with arginine or with a mixture of arginine/lysine polypeptides affords higher CDN‐packaging capacity and leads to higher activation of IFN‐I and the nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) proinflammatory signaling pathway. In the B16‐F10 murine model of melanoma, the intratumoral administration of a synthetic CDN via arginine‐modified G5‐PAMAM dendrimers at a low dose induces strong antitumor responses and inhibits tumor growth. It is also shown that the combination of this therapy with immune checkpoint blockade (ICB) further improves the therapeutic outcomes. Cationic polypeptide dendrimers may be advantageous in the delivery of gene‐based immunomodulators for the treatment of solid tumors. Abstract : Herein, a library of polypeptide‐modiifed dendrimers is developed to efficiently deliver cyclic dinucleotide (CDN). Arginine‐modified dendrimers (D‐CR3) show higher CDN packaging capacity, higher type‐I interferon (IFN‐I), and reduced toxicity compared to unmodified dendrimers. Intratumoral administration of CDN (0.5 μg) using a D‐CR3 dendrimers in a melanoma model induces an inhibition of tumor growth and enhances survival.